"Finger-tip" cryotherapy probes: treatment of squamous and melanocytic conjunctival neoplasia. Issue 8 (15th July 2005) - Finger, P T
Abstract : Aim: To describe the use of a new spatulated cryoprobe in treatment of conjunctival neoplasia. Methods: A new cryoprobe design was submitted to Mira, Inc resulting in new hand held probes capable of producing homogeneous freezing over large surface areas. The active surface of the small, medium, and large spatulated probes are 8.5 mm 2, 25.2 mm 2, and 70 mm 2 . End freezing reduces the possibility of inadvertent freezing of adjacent tissues (outside the targeted zone). In this series, the probes were employed to treat patients with squamous and melanocytic conjunctival neoplasia. Results: 12 consecutive patients with malignant conjunctival neoplasia were treated with these new cryotherapy probes. Techniques of probe construction and clinical use are described. Cryoburns of the cornea, sclera, and conjunctiva were formed and recorded by digital photography. Ophthalmic examinations before and after surgery demonstrated that no acute intraocular or adnexal complications occurred. No loss of visual acuity could be attributed to this use of the cryoprobes. Conclusion: "Finger-tip" cryoprobes were used to treat malignant conjunctival neoplasia (squamous and melanocytic). Probe design allowed for uniform freezing over large surface areas. This cryoprobe design appears to be ideal for treatment of conjunctival tumours.